(untitled) (International Seven Journal of Multidisciplinary, 2026)
In the context of stomatology and head and neck surgery, ameloblastoma plays a prominent role. Although defined by the World Health Organization (WHO) as a benign entity, it exhibits biologically aggressive behavior, characterized by an infiltrative growth pattern and high recurrence rates, which demands an in-depth understanding of its pathogenic and clinical aspects to achieve a favorable prognosis. Ameloblastoma is an odontogenic neoplasm of epithelial lineage that, despite being histologically benign according to the WHO, displays a biological phenotype marked by aggressive medullary infiltration, progressive expansion, and elevated recurrence rates. The complexity of clinical management lies in the dichotomy between complete eradication of tumor margins and preservation of the functional and aesthetic integrity of the stomatognathic system. The analysis of contemporary therapeutic modalities indicates that the transition between conservative interventions and radical resections should be based on rigorous mapping of the histopathological subtype and the cortical extent of the lesion. In parallel, the integration of molecular biomarkers and immediate prosthetic reconstruction techniques redefines prognosis, enabling an approach that goes beyond strict oncological control. Clinical resolution and mitigation of tumor recurrence depend on individualized management, with particular attention to patient age and specific tumor biology. It is imperative that therapeutic outcomes be supported by longitudinal surveillance protocols and multidisciplinary rehabilitation, ensuring morphofunctional restoration and long-term preservation of quality of life.